(untitled) (Intent Research Scientific Journal, 2023)
In the current era of information globalization, the changes taking place in the field of education directly change his activity from teacher to active, adapting to the same process of globalization, requiring continuous independent work. Emphasis is placed on the fact that in order to implement the modern values of education, a new teacher is needed - a professional teacher. In this article, attention is paid to these characteristics of the teacher.